The Revival Movement In Uganda: An Evaluation - Ndyabahika, James (African Journal of Evangelical Theology, 1993)
Answering critics of the East Africa Revival the author retells the story of this powerful awakening and examines the theology proclaimed by the Revival Movement in Uganda. He examines the teaching of the movement on Christ, conversion, the Spirit and the Word. He concludes that "critics need to be reminded that the revival movement is the work of God. Since Pentecost, God has been using revivals in spreading Christian renewal throughout the world. In this regard, the Revival Movement is not outmoded in our generation. "